The Role and Challenges of Digital Leadership in Health Human Resource Management: A Systematic Literature Review - Putra, Gede Ngurah Prasetya Adhitama (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2025)
The accelerating digital transformation in healthcare has significantly influenced human resource management (HRM), with digital leadership emerging as a critical factor in navigating AI-driven workforce systems. However, there remains a research gap regarding the specific role of digital leadership in optimizing HRM, addressing workforce resistance, and ensuring ethical AI integration. This study conducts a systematic literature review (SLR) of 18 high-impact articles sourced from Scopus, Web of Science, PubMed, and Google Scholar, aiming to explore how digital leadership influences AI integration, workforce automation, and leadership challenges in healthcare institutions. The review identifies key themes, including the impact of digital leadership on workforce efficiency, talent retention, and strategic HRM decision-making. Findings reveal that while AI-driven HRM practices—such as predictive analytics and automated recruitment—enhance operational performance, they also pose risks related to data privacy, algorithmic bias, and job displacement. The study highlights regional disparities, where developed nations prioritize AI ethics and data governance, while developing countries face infrastructural and digital literacy challenges. By synthesizing best practices in leadership adaptability, ethical AI deployment, and digital upskilling, the study provides actionable insights for healthcare leaders and HR professionals. This research contributes to the academic discourse by offering a comprehensive framework for responsible and sustainable AI-driven HRM transformation. It emphasizes the importance of strategic digital leadership in overcoming resistance, aligning workforce capabilities with technological advancements, and ensuring equitable implementation across diverse healthcare systems.